Standardization of agronomic practices of fennel for sowing in Poplar and Eucalypts plantation - Kaur, Gagandeep; Gill, Rishi I.S.; Singh, Baljit; Singh, Thakar (Indian Journal of Agroforestry, 2020)
The performance offennel (Foeniculum vulgare Mill.), a high value crop was studied under poplar (PopulusÂ deltoides Bartr.) and eucalypts (Eucalyptus tereticornis Smith) plantation. The treatments consisted of three environments (poplar, eucalypts and open conditions) and six combinations of three sowing times (last week of October, first week of November and third week of November) and two fertilizer dozes [recommended (50 kg/ha N) and 50% more than recommended (75 kg/ha N)]. Growth attributes and yield of fennel were significantly affected by environments and treatments. Mean maximum grain yield of fennel was recorded in open conditions (4.6 Mg /ha) followed by poplar (3.8 Mg/ha) and eucalypts (3.4 Mg /ha) block plantation. The grain yield decreased significantly with the delay in sowing from the last week of October (5.3 Mg/ha) to 3rd week of November (2.5 Mg/ha). Grain yield responded positively to additional doze of fertilizer at all the sowing dates. Positive relationship was observed between different growth attributes and the grain yield of fennel. The nutrient uptake (N, P and K) was the highest in open followed by poplar and eucalypts plantation. The nutrient uptake reduced with delay in sowing and improved by additional doze of fertilizers. Poplar + fennel based agroforestry system could be exploited as one of the economically viable alternatives for resource exhaustive rice-wheat cropping system.